2013
DOI: 10.1074/jbc.m113.466052
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary KChIP4a Suppresses A-type K+ Current through Endoplasmic Reticulum (ER) Retention and Promoting Closed-state Inactivation of Kv4 Channels

Abstract: Background:Compared with other auxiliary KChIPs that enhance Kv4 current, KChIP4a inhibits Kv4 function. Results: We identified an ER retention motif and an adjacent VKL motif within the KChIP4a N terminus that reduces Kv4.3 surface expression and promotes closed-state inactivation (CSI), respectively. Conclusion: ER retention and CSI enhancement are two distinct mechanisms by which the N terminus of KChIP4a suppresses Kv4 function. Significance: This study provides mechanistic insight into auxiliary KChIP4a-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 90 publications
3
33
0
Order By: Relevance
“…The peak currents of Kv4.3 coexpressed with two or four KChIP4a were significantly reduced in a KChIP4a-dependent manner, as compared with Kv4.3 alone (Fig. 5 A, right panel, and Table 1), consistent with literature for KChIP4a that reduces Kv4 current (7). In contrast, coexpression of tandem Kv4.3 and KChIP4a complex with KChIP4bl that functions like KChIP1 (22), the current of channel complex was increased to 5.…”
Section: Gating Properties Of Kv43-kchip4 Complexessupporting
confidence: 90%
See 3 more Smart Citations
“…The peak currents of Kv4.3 coexpressed with two or four KChIP4a were significantly reduced in a KChIP4a-dependent manner, as compared with Kv4.3 alone (Fig. 5 A, right panel, and Table 1), consistent with literature for KChIP4a that reduces Kv4 current (7). In contrast, coexpression of tandem Kv4.3 and KChIP4a complex with KChIP4bl that functions like KChIP1 (22), the current of channel complex was increased to 5.…”
Section: Gating Properties Of Kv43-kchip4 Complexessupporting
confidence: 90%
“…KChIP4bl (also known as KChIP4.1) that only differs in its N-terminus with other KChIPs increases Kv4 current density, slows inactivation, and accelerates the speed of recovery from inactivation (22). In contrast, the KChIP4 splice variant KChIP4a (also known as KChIP4.4) that functions as a suppressor of Kv4 channels decreases Kv4 current density and slows open-state inactivation and recovery from inactivation (4,7,(23)(24)(25). Interestingly, gene-specific alternative splicing shifts from KChIP4bl to KChIP4a that leads to inhibition of the Kv4 function can increase secretion of b-amyloid (26), suggesting a role of differential expression of KChIP isoforms and their variable subunit compositions with Kv4 in the pathogenesis of the brain such as etiology of neurodegenerations.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, KChIP4a completely suppresses the fast macroscopic inactivation of Kv4 channels, resulting in delayed rectifier-like currents [15]. The N-terminal KIS domain of KChIP4a, which also harbors an ER retention motif, is made responsible for these trafficking and gating effects [15,81]. In the KChIP4a splice variant the hydrophobic groove, which represents a binding domain of KChIPs for the Kv4 N-terminal helix [30,75,82], can be occupied by its own N-terminal helix in vitro (Figure 2(c)), and it was suggested that it may have to be competed out by the Kv4 N-terminus to allow Kv4/KChIP4a complex formation [83,84].…”
Section: Ca2+ Dependence Of Kv4/kchip Complex Formation and Membrane mentioning
confidence: 99%